2019
DOI: 10.3390/medicina55090579
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Renoprotective Properties of Lovastatin-Loaded Ginger and Garlic Oil Nanoemulsomes: Insights into Serum Biological Parameters

Abstract: Background and Objectives: Dyslipidemia is gaining much attention among healthcare professionals because of its high association with the malfunctioning of a number of normal physiological and metabolic processes in the body. Obesity is directly interconnected with dyslipidemia and is said to be a denouement of hyperlipidemia and, if left untreated, may lead to intense damage to organs that are directly involved in fat metabolism. The objective of this study was to investigate the synergistic antiobesity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 88 publications
(107 reference statements)
4
6
0
Order By: Relevance
“…Moreover, serum creatinine, urea and uric acid that were measured to evaluated functional kidney damage were significantly increased in HFD fed group than control. These results concurred with Faran et al (2019) . Elevated liver and kidney enzymes were an expected result of increased MDA during obesity, which is an indicator for extensive lipid peroxidation.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, serum creatinine, urea and uric acid that were measured to evaluated functional kidney damage were significantly increased in HFD fed group than control. These results concurred with Faran et al (2019) . Elevated liver and kidney enzymes were an expected result of increased MDA during obesity, which is an indicator for extensive lipid peroxidation.…”
Section: Discussionsupporting
confidence: 89%
“…The present study demonstrated that exercise may exert a protective effect against kidney damage induced by hyperlipidemia, including limiting the progression of lipid deposition, oxidative stress and fibrosis. Compared with in ApoE -/- mice that consumed a ND, higher LDL-c, TG and TC levels were observed in ApoE -/- mice that consumed a HD, in agreement with Faran et al ( 16 ). Furthermore, CRE levels were higher in the HD group compared with those in the ND group.…”
Section: Discussionsupporting
confidence: 90%
“…Weight gain is caused by an imbalance between energy uptake and energy expenditure that causes TG accumulation in white adipose tissue (WAT) [35] and other non-adipose tissues, such as muscle, liver, kidneys and heart [36]. Our data are consistent with that of Buettner et al [37] and Ali Faran [38], who have shown that an increase in body weight can be observed after only four weeks of HFD, while other authors indicate that a longer period of high-fat diet intake is needed for weight changes in animals [39]. Crawford et al showed that the HFD regime applied to 6-week old Spraque Dawley rats increased their body mass index (BMI) and fasting glucose levels [24], which was also confirmed in Wistar rats [40].…”
Section: Plos Onesupporting
confidence: 90%